Effects of Conferring Business Resource on Rivals - Tejaswi Channagiri Ajit; Mark A. Jamison (International Telecommunications Society (ITS), 2022)
We examine how requiring platforms to give rivals resources, such as data, affects innovation. Using simulations in which an initial firm obtains a head start on rivals and uses that head start to build a valuable resource that subsequently gives it a competitive advantage over rivals when competing in the initial technology, we contrast scenarios in which the initial firm is or is not required by a government regulator to provide this resource to rivals. We develop pricing provisions that incentivize the initial firm to voluntarily provide the resource to rivals. We then contrast incentives to create substitutes for the initial technology.
Keywords: L13; L15; L51; 330; platforms; innovation; competition